(untitled) (Marketing Journal, 2026)
This article investigates the issues of improving strategic management mechanisms for innovative activity in the construction industry. The study highlights the role of strategic planning, digital transformation, investment approaches, and modern managemen t methods in ensuring the innovative development of construction enterprises. Special attention is given to enhancing the competitiveness of the construction sector, increasing production efficiency, and forming sustainable development factors through inno vation implementation.